Economic Interests, Worldviews and Identities: Theory and Evidence on Ideational Politics - Elliott Ash; Sharun Mukand; Dani Rodrik (Center for Economic Studies and ifo Institute (CESifo), 2021)
We distinguish between ideational and interest-based appeals to voters on the supply side of politics, and integrate the Keynes-Hayek perspective on the importance of ideas with the Stigler-Becker approach emphasizing vested interests. In our model, political entrepreneurs discover identity and worldview "memes" (narratives, cues, frames) that shift beliefs about voters' identities or their views of how the world works. We identify a complementarity between worldview politics and identity politics and illustrate how they may reinforce each other. Furthermore, we show how adverse economic shocks may result in a greater incidence of ideational politics. We use these results to analyze data on 60,000 televised political ads in U.S. localities over the years 2000 through 2018. Our empirical work quantifies ideational politics and provides support for the key model implications, including the impact of higher inequality on both identity and worldview politics.
Keywords: D72; P16; 330; economic interests; identity; narratives; ideational politics